Effect of sample deformation in longitudinal axis on material parameter extraction by waveguides. (May 2021) - Hasar, Ugur Cem; Kaya, Yunus; Ozturk, Gokhan; Ertugrul, Mehmet
Abstract: An analysis was performed for examining the consequences of sample deformation in longitudinal axis in the sample-loaded non-resonant waveguide techniques. Vertical and horizontal deformations were first simulated to understand the change in field distributions and corresponding scattering parameters. Then, effects of sample length, dielectric constant, and loss factor for these deformations on extracted electromagnetic properties were analyzed using simulated results. Finally, S-parameter measurements were carried out to understand the effect of vertical deformation on permittivity results and to examine any improper sample preparation by hand-made and machine-made samples by applying a statistical model based on mean, standard deviation, coefficient of variation, and confidence interval. It was noted that extracted dielectric constants of each tested dielectric sample (polyethylene, polypropylene, polyvinyl-chloride) were within the confidence interval range of 90% while their retrieved loss factors were within the confidence interval range of 90%, 95%, or 98%. Highlights: Effect of sample deformation in the longitudinal axis is comprehensively analyzed. Effects of sample length, dielectric constant, and loss factor are simulated. Effect of sample deformation by the statistical metrics is examined via measurements. Extracted dielectric constant values are noted within the confidence interval of 90%. Retrieved loss factor values are noted within the confidence interval of 90-98%.